A Complex Zeolite Containing Multiple Ring Sizes in a Single Channel: One‐Dimensional Zeolite UZM‐55. Issue 67 (8th November 2018) - Mowat, John P. S.; Miller, Mark A.; Galey, Melissa M.; Sinkler, Wharton; Prabhakar, Sesh; Xu, Lijun; Nicholas, Collette L.; Nicholas, Christopher P.
Abstract: Zeolites are porous aluminosilicate materials utilized in a variety of sorption, separation, and catalytic applications. The oil refining industry in particular has seen a number of significant advances due to the introduction of new technologies enabled by new zeolites. Of particular importance are zeolites with 10‐ or 12‐membered ring pores, resulting in pore shapes and sizes appropriate for the interaction with small hydrocarbon molecules. Here, the synthesis of a new zeolite UZM‐55 is reported and the idealized structure thereof is presented. The most complex structure solved to date, UZM‐55 possesses a large triclinic unit cell containing 52 T‐sites. The material uniquely contains both 10‐ and 12‐membered ring pores in a single, undulating one‐dimensional channel, the first example in a zeolitic material of multiple delimiting rings in a single channel. This discovery opens new opportunities in shape‐selective adsorption and catalysis. Demonstrated here is the unique adsorption behavior of UZM‐55, shown both experimentally and computationally to adsorb one nonane molecule per unit cell in a linear conformation. Abstract : A complex tale : The synthesis and structure solution of UZM‐55, the most structurally complex zeolite thus known, is reported. UZM‐55 is the first zeolite structure solved in P1, contains 52 independent T‐sites and a unique, undulating pore channel with both 10‐ and 12‐membered delimiting rings present in the same pore. Computational results show that nonane is adsorbed in a linear conformation with no kink defects within the pore, confirming the n‐nonane experimental results.